Quality Advantage? Provider Quality and Networks in Medicare Advantage (Journal of Public and Nonprofit Affairs, 2020)
Medicare Advantage plans have grown significantly over the past decade and the potential for their future growth seems unabated. Astonishingly, however, we know little about how Medicare beneficiaries access services, particularly whether those services are of high quality. This study explores access to cardiac surgeons for coronary artery bypass grafting (CABG) and heart valve surgery in California and New York. It is one of the first studies to analyze Medicare Advantage networks and interactions between provider networks and provider quality. Results of the study show that for large metropolitan areas, access is rather similar for traditional Medicare and Medicare Advantage beneficiaries. Limitations, however, exist for the latter. Important concerns emerge for Medicare Advantage beneficiaries outside of metropolitan areas where healthcare market challenges appear to be exacerbated by carrier restrictions. Results indicate no evidence that carriers selectively contract to improve quality. There is, however, significant diversity with regard to network breadth; and, this breadth does not stay static across distances. These results hold important implications for the future of the Medicare program, network adequacy regulations, and how consumers make choices about their insurance coverage.